IMPLEMENTATION OF EARLY MARRIAGE PREVENTION EDUCATION USING SHORT FILMS IN SIDOREJO VILLAGE: Implementasi Edukasi Pencegahan Pernikahan Dini Menggunakan Film Pendek Di Desa Sidorejo - Wapa, Andi; Harun Arrasyid; Uswatun Hasanah; Ira Nur Aini; Nuril Lailatuz Zaqiyah (Jurnal Mitra Dedikasi Masyarakat, 2025)
This community service program aimed to increase adolescents’ knowledge and awareness regarding the prevention of early marriage through short films and health education counseling in Sidorejo Village. The activities were carried out using educational film screenings, delivery of reproductive health materials, and interactive discussions with participants. The program was implemented as planned and received a positive response from the community, as evidenced by active participant engagement and support in providing facilities and infrastructure. The results indicated that adolescents gained a better understanding of the economic, social, and health impacts of early marriage. In addition, low economic conditions were identified as a major contributing factor to early marriage in Sidorejo Village. The evaluation results suggest the need for similar follow-up programs to be conducted periodically, with expanded target groups, particularly involving parents of adolescents, given their crucial role in family education and decision-making. Overall, this program is expected to contribute to efforts to promote marriage age maturity and improve adolescents’ reproductive health awareness in the community